2010
DOI: 10.1111/j.1834-7819.2009.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative activity of cells from remaining dental pulp in response to treatment with dental materials

Abstract: Background: The biological examination of pulp injury, repair events and response of dental pulp stem cells to dental restorative materials is important to accomplish restorative treatment, especially to commonly used dental materials in paediatric dentistry, such as glass ionomer cement (GIC) and calcium hydroxide (Ca(OH) 2 ) lining cement. Methods: Healthy patients aged between 9 to 11 years with carious primary molars without pulp exposure were selected and divided into two groups: Group 1 (teeth restored w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Moreover, the information obtained is both qualitative and quantitative (Lutfi et al . ). With Biodentine and MTA Angelus, the MSC surface molecules, CD73, CD90 and CD105, were expressed at levels >95%, whereas the expression of the haematopoietic markers, CD34 and CD45, was <5%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the information obtained is both qualitative and quantitative (Lutfi et al . ). With Biodentine and MTA Angelus, the MSC surface molecules, CD73, CD90 and CD105, were expressed at levels >95%, whereas the expression of the haematopoietic markers, CD34 and CD45, was <5%.…”
Section: Discussionmentioning
confidence: 97%
“…In very deep cavities with remaining dentine thickness between 0.25 and 0.01 mm or in pulp exposure cavities, dental pulp stem cells proliferate, migrate to the site of injury and differentiate to form odontoblastoid cells (Lutfi et al . ). Cell migration is necessary for homoeostatic tissue maintenance and the regeneration of injured organs and tissues (Rennert et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lutfi et al showed that glass ionomer cement (GIC) as a lining material can act similar to Ca(OH) 2 in inducing proliferative activity in dental pulp of exfoliated deciduous teeth 51) . Dammaschke et al compared the effect of dentine adhesive Gluma Comfort Bond (GCB) and Ca(OH) 2 on the proliferation of pulp cells and concluded that GCB, due to its missing antibacterial efficacy and foreign body reactions, causes the inflammation of pulp tissue.…”
Section: The Effect Of Dental Treatments and Materials On Angiogenesimentioning
confidence: 99%
“…It is important to study the properties of different capping materials in the context of cell viability of regenerating cells, transcriptional profile and their ability to affect differentiation process. Calcium Hydroxide [Ca(OH) 2 ] is commonly used for direct pulp capping with sufficient biological responses [37]. However, the main disadvantages of Ca(OH) 2 are weak cohesive strength, marginal leakage and inadequate antibacterial effect [2].…”
Section: Introductionmentioning
confidence: 99%